Alveolar ridge augmentation using distraction osteogenesis: a clinical trial - Anand Shukla; Saumyendra V Singh; Sumit Kumar; Divya Mehrotra; S Mohammad; Stuti Singh (Journal of Oral Biology and Craniofacial Research)
ABSTRACT: Background: Severely resorbed ridges present a great challenge to prosthodontic rehabilitation. Available reconstructive options include autologous/alloplastic augmentation with questionable results, or regeneration of new bone under gradual and controlled tension using distraction osteogenesis. This study focused on use of distraction osteogenesis for the treatment of vertically deficient alveolar ridges to assess its feasibility and outcome. Materials and Methods: Alveolar distraction osteogenesis (ADO) was studied at 10 different intra-oral, partial or complete edentulous sites. After a latency period of 5 days, distraction was carried out for 6–7 days at the rate of 0.5 mm every 12 hours (1 mm/day). Distractor was removed after a consolidation period of 12 weeks. Results: The mean height gained at the 10 intra-oral sites was 4.8 mm with standard deviation of ± 0.056. The mean follow-up period was 2 years. Complications of therapy included hardware failure, wound gape and extra-oral scar. The overall complication rate was 10%. Conclusion: Distraction osteogenesis is a promising option to aid uneventful prosthodontic rehabilitation of severe vertically resorbed alveolar ridges.